(untitled) (Bangladesh Journal of Otorhinolaryngology, 2023)
Papillary thyroid carcinoma (PTC) is commonly associated with praising survivaland less recurrence rate compared with other malignancy. The prognosis of PTC depends on age, sex, size of tumor, lymphadenopathy, and extrathyroidal extension. PTC which invade upper aerodigestive tract (ADT) is more aggressive tumor that signify the patients at a greater risk of recurrence and death. Bangladesh J Otorhinolaryngol 2023; 29(1): 45-48